KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI LARUTAN PENYANGGA MENGGUNAKAN METODE PRAKTIKUM VIRTUAL - Kurnia Sandi; Yuni Fatisa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Basically, students had critical thinking skills in learning such as questioning, hypothesizing, clarifying, observing, and interpreting. In fact, these skills sometime were not developed well, so it was needed a method that was able to develop student critical thinking skills. This research aimed at analyzing student critical thinking ability through virtual practical work method. It was conducted in the eleventh grade of Natural Science one at Islamic Senior High School of Yaspika Karimun. Descriptive method was used in this research with one shot case study design. The samples were one of two classes, and Purposive sampling technique was used in this research. Instruments of this research were essay test and observation sheet. The data analysis results showed that the mean percentage of critical thinking ability of the eleventh-grade students of Natural Science 1 at Islamic Senior High School of Yaspika Karimun on Buffer Solution lesson was 74.34% with good category for test instrument, and the mean percentage of observation sheet instrument was 76.67% with good category. Based on these findings, it could be concluded that student critical thinking skills with Virtual Practical Work method on Buffer Solution lesson was on good category.Keywords : Critical Thinking Ability, Virtual Practical Work Method, Buffer Solution